Design selection for new In-Flight food delivery and waste collection system of commercial passenger transport aircraft using TOPSIS - Ishak, Farah Diana; Romli, Fairuz Izzudin (Universiti Teknologi MARA (UiTM), 2021)
One of the important airline services that can influence the passengers’ loyalty is the in-flight meal service. In this study, the conceptual design process of new in-flight food delivery and waste collection system is carried out using the standard engineering design method to improve the current system. A critical step in this process is the design concept evaluation and selection where the best alternative design concept solution is chosen for further development. The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method is applied to facilitate the selection process of the best design concept for the new improved in-flight food delivery and waste collection system. The design evaluation criteria for the TOPSIS assessment procedures are taken from previous work done on design requirements analysis for the new in-flight food delivery and waste collection system. Similarly, five alternative design concepts for the new system are taken from the results of the previous research work done. Furthermore, an online public survey is conducted to acquire the assessment rating of all alternative design concepts for each design evaluation criterion. The assessment rating is assigned using a simple Likert rating scale. From the resultant TOPSIS ranking, Concept 3 has emerged as the best design concept with a closeness rating of 0.9589, which is very close to 1. For future research work, this selected final design concept for the new in-flight food delivery and waste collection system will be forwarded to the next engineering design stage for further development.